The Effect of Leaf Applications “Bio-fertilizers” on Yield and Some Yield Components of Wheat at Different Development Periods - Hayati Aslan; Hatun Barut; Sait Aykanat; Enis G Hekimoğlu (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to determine the effects of “biofertilizers” (N 8%, P2O5 1%, 9% K2O, 3% Iron, 0.06% Zinc, Bacillus subtilis (GBO3), Bacillus subtilis, Bacillus licheniformis, Bacillus amyloliquefaciens ve Bacillus pumilus) eaf applications on yield and quality parameters of bread wheat at different developmental stages. The experiment carried out for this purpose was conducted in the wheat sowing seasons of 2017-2018 and 2018-2019 at Doğankent location of the Eastern Mediterranean Agricultural Research Institute. In this research, “biofertilizers” leaf applications were applied to the wheat in different stages of development. For this purpose, 4 themes were worked out as; control, tillering, tillering + stem elengation and stem elengation. Biofertilizers doses of 100 gr/da in the first year and 0.75 gr/da in the second year were investigated. As a basic fertilizer for all experiment subjects; 15 kg DAP per decar were given during sowing period and 29 kg Urea during the tillering period, as a result of the research carried out; using biofertilizers in wheat farming, both in tillering and stem elengation periods, increased the yield 12.67% more efficiency in the first year and 13.16% more in the second year than the control subject. There were no statistically significant effects on quality parameters of wheat by using “biofertilizers” in foliar applications.